2010
DOI: 10.1111/j.1365-2710.2010.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mechanism(s) of action of natural products: analgesic peroxide oil as example

Abstract: Summary Background:  There are multiple reports of natural products having therapeutic effect. In an era of evidence‐based medicine, clinical trials inform clinical decisions regarding use of the product, but prevailing preference is to identify and use a single ‘active ingredient’. Yet, the clinical benefit of a natural product might derive from the fortuitous combination of its multiple components. Therefore, the elucidation of the mechanism(s) of action of natural products is important, but presents signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 151 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…As no single analgesic drug is ideal for all pains (Pirmohamed et al, 2004), additional therapies are always being sought. According to Raffa and Pergolizzi (2011), natural products might contain ingredients that offer such alternatives by acting through novel mechanisms of action or by interacting additively or synergistically through known mechanisms of action. The results of the present study revealed that, IE and CE extracts showed analgesic action in mice, by inhibiting the acetic acid-induced writhing as compared to the positive drug indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…As no single analgesic drug is ideal for all pains (Pirmohamed et al, 2004), additional therapies are always being sought. According to Raffa and Pergolizzi (2011), natural products might contain ingredients that offer such alternatives by acting through novel mechanisms of action or by interacting additively or synergistically through known mechanisms of action. The results of the present study revealed that, IE and CE extracts showed analgesic action in mice, by inhibiting the acetic acid-induced writhing as compared to the positive drug indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…Although, an intact ring H and a free C-25-OH group are both essential for overall in vitro activity (proliferation, migration and invasion assays), their modification does not necessarily abolish molecular mechanisms. These results point both to the complex structural requirement and molecular mechanisms through which penitrems exert their effects, which is the case with most natural products [39,40]. …”
Section: Resultsmentioning
confidence: 99%
“…An OGT‐product has been commercially available in Europe for over a decade and has recently become available in the United States (OxyRub™; Creomed). Although its exact mechanism of action remains to be elucidated, its analgesic and anti‐inflammatory effects may involve the reduction in one or both of the mechanisms of lipid peroxidation of the arachidonic acid cascade 46 . Lipid peroxidation is pathological and reactive oxygen scavengers can be used pharmacologically to interrupt this process.…”
Section: Discussionmentioning
confidence: 99%